WISH FOR THE FUTURE AND ACTIVE ENGAGEMENT IN LIFE: AN ECOLOGICAL MOMENTARY ASSESSMENT STUDY - Liu, T (Innov Aging, 2018)
Engagement in meaningful and productive activities has long been thought to relate to successful aging, yet its association with older adults’ wishes for the future has rarely been examined. This cross-sectional study recruited 369 community-dwelling older adults in Hong Kong. Trained researchers interviewed them for demographics, wishes for the future, cognition using Cantonese Mini-Mental State Examination (C-MMSE), frailty, and followed up with a 7-day ecological momentary assessment (EMA). Participants (age 75 ± 8.4 years; 79% women) had low education (64% no formal education) and normal cognition (C-MMSE 27 ± 2.8), and majority were healthy (55% robust). Wishes for the future were coded into six categorizes based on content analysis: 23 (6%) reported no wish because of “despair”, 40 (11%) no wish and “living for now”, 47 (13%) no wish because “all fulfilled”, 99 (27%) have “wishes only for self”, 125 (34%) “wishes for family members”, and 25 (9%) “wishes for society”. EMA data was coded and percentage of leisure and productive activities out of all activities indicated active engagement (.67±.11). ANCOVA revealed that after controlling for demographics, cognition and frailty, wishes for the future was significantly associated with active engagement (F(5,368)=3.5, p<.05). Planned comparisons suggested that “wishes for family members” group was more active than “despair” (F(1, 141)=7.34, p<.01), “living for now” (F(1, 158)=7.64, p< .01), and “wish only for self” (F(1,216)=12.28, p<.01) groups. Our findings suggest that wishes for future are associated with engagement in current life, and promotion of successful aging may consider addressing the issue of fostering wishes and hopes.